Phase 1 study of high-dose DFMO, celecoxib, cyclophosphamide and topotecan for patients with relapsed neuroblastoma: a New Approaches to Neuroblastoma Therapy trial - Michael D. Hogarty; David S. Ziegler; Andrea Franson; Yueh‐Yun Chi; Denice Tsao‐Wei; Kangning Liu; Rohan Vemu; Eugene W. Gerner; Elizabeth Bruckheimer; Anasheh Shamirian; Beth Hasenauer; Frank M. Balis; et al. (2024)
Abstract Background MYC genes regulate ornithine decarboxylase (Odc) to increase intratumoral polyamines. We conducted a Phase I trial [NCT02030964] to determine the maximum tolerated dose (MTD) of DFMO, an Odc inhibitor, with celecoxib, cyclophosphamide and topotecan. Methods Patients 2–30 years of age with relapsed/refractory high-risk neuroblastoma received oral DFMO at doses up to 9000 mg/m 2 /day, with celecoxib (500 mg/m 2 daily), cyclophosphamide (250 mg/m 2 /day) and topotecan (0.75 mg/m 2 /day) IV for 5 days, for up to one year with G-CSF support. Results Twenty-four patients (median age, 6.8 years) received 136 courses. Slow platelet recovery with 21-day courses (dose-levels 1 and 2) led to subsequent dose-levels using 28-day courses (dose-levels 2a-4a). There were three course-1 dose-limiting toxicities (DLTs; hematologic; anorexia; transaminases), and 23 serious adverse events (78% fever-related). Five patients (21%) completed 1-year of therapy. Nine stopped for PD, 2 for DLT, 8 by choice. Best overall response included two PR and four MR. Median time-to-progression was 19.8 months, and 3 patients remained progression-free at >4 years without receiving additional therapy. The MTD of DFMO with this regimen was 6750 mg/m 2 /day. Conclusion High-dose DFMO is tolerable when added to chemotherapy in heavily pre-treated patients. A randomized Phase 2 trial of DFMO added to chemoimmunotherapy is ongoing [NCT03794349].